SLOVAKIA FORCED STERILIZATION ON RROMA WOMEN PRACTICES. AN ETHICAL CASE ANALYZE - ALUAȘ, Maria (Studia Universitatis Babeş-Bolyai Bioethica, 2015)
The paper presents some ethical considerations regarding forced sterilization practice on Roma women in some countries in Eastern Europe, a case from Slovakia. These practices are done by decades in same countries and Slovakia was the first case jugged by the European Court of Human Rights in Strasbourg, France. Thinking to the facts we realize that we are facing with huge risks for patients and not only for Roma people, but for all us. Patients go to the doctors because of his or her profession, and because they are sick and they need help. They do not go to doctors because of his or her personal opinion on something, and if doctors do not act for patients good, patients will lose trust and confidence and they will be afraid to go to the hospital. Today we talk about Roma people, but who knows what kind of discrimination criteria will be tomorrow, or in few years? We need doctors who do their job in a proper way and who knows very well the nature of their profession and its limits. This is the take-away message from this case. Practici de sterilizare forțată a femeilor de etnie romă în Slovacia. O analiză etică. Acest articol prezintă câteva considerații etice referitoare la practica de sterilizare forțată a femeilor de etnie romă în unele țări din Europa de Est (cazul Slovaciei). Aceste practici sunt efectuate de zeci de ani în anumite țări, Slovacia fiind primul caz judecat la Curtea Europeană a Drepturilor Omului de la Strasbourg, Franța. Gândindu-ne la aceste fapte ne dăm seama că ne confruntăm cu riscuri imense pentru pacienți și nu numai pentru cei de etnie romă, ci pentru noi toți. Pacienții merg la medici în considerentul profesiei lor, pentru că sunt bolnavi și au nevoie de ajutor. Ei nu merg la medici, din cauza opiniei personale a acestora cu privire la ceva, iar dacă medicii nu acționează pentru binele pacienților, aceștia își vor pierde încrederea și le va fi frică să meargă la spital. Astăzi vorbim despre persoane de etnie romă, dar cine știe ce fel de criterii de discriminare vor fi mâine, sau în câțiva ani? Avem nevoie de medici care să-și exercite profesia, în mod corespunzător, și care să cunoască foarte bine natura profesiei lor și a limitelor acesteia. Acesta este mesajul de reținut din acest caz. Cuvinte cheie: practici de sterilizare forțată, femei de etnie romă, principii bioetice, aspecte legale, consimțământ informat.